SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN OBYEK WISATA TERBAIK DI KABUPATEN SRAGEN DENGAN METODE WEIGHTED PRODUCT - Muqorobin Muqorobin; M Hasan Ma'ruf (Politeknik Bisnis Indonesia, 2022)
Sragen Regency Tourism Object is one of the places for recreation with family. Sragen Regency has many beautiful and diverse tourist attractions, making it difficult for people to determine the best tourist attraction. The criteria that are in great demand by the public are: Location, Facilities, Tickets and Security. This requires the Head of the Tourism Office to be able to make decisions in determining the best tourism objects. The purpose of this research is to make a Decision Support System Application for the Selection of the Best Tourist Attractions in Sragen Regency by using the Weighted Product Algorithm Method. This method was chosen because it has the ability to rank to determine the best alternative based on all criteria and weights. Data was collected by means of interviews, observations and literature studies. System design is made with Context Diagram, HIPO, DAD and ERD. This application was developed with PHP language and MySQL database. The results of the tests carried out on the functionality test were good and the validity test results were 100% valid. The implementation results obtained by the best tour is Ndayu Park with the highest score of 0.0852.